A dynamic H3K27ac signature identifies VEGFA-stimulated endothelial enhancers and requires EP300 activity - Zhang, Bing; Day, Daniel S.; Ho, Joshua W.; Song, Lingyun; Cao, Jingjing; Christodoulou, Danos; Seidman, Jonathan G.; Crawford, Gregory E.; Park, Peter J.; Pu, William T. (Genome Research, 2013)
Histone modifications are now well-established mediators of transcriptional programs that distinguish cell states. However, the kinetics of histone modification and their role in mediating rapid, signal-responsive gene expression changes has been little studied on a genome-wide scale. Vascular endothelial growth factor A (VEGFA), a major regulator of angiogenesis, triggers changes in transcriptional activity of human umbilical vein endothelial cells (HUVECs). Here, we used chromatin immunoprecipitation followed by high-throughput sequencing (ChIP-seq) to measure genome-wide changes in histone H3 acetylation at lysine 27 (H3K27ac), a marker of active enhancers, in unstimulated HUVECs and HUVECs stimulated with VEGFA for 1, 4, and 12 h. We show that sites with the greatest H3K27ac change upon stimulation were associated tightly with EP300, a histone acetyltransferase. Using the variation of H3K27ac as a novel epigenetic signature, we identified transcriptional regulatory elements that are functionally linked to angiogenesis, participate in rapid VEGFA-stimulated changes in chromatin conformation, and mediate VEGFA-induced transcriptional responses. Dynamic H3K27ac deposition and associated changes in chromatin conformation required EP300 activity instead of altered nucleosome occupancy or changes in DNase I hypersensitivity. EP300 activity was also required for a subset of dynamic H3K27ac sites to loop into proximity of promoters. Our study identified thousands of endothelial, VEGFA-responsive enhancers, demonstrating that an epigenetic signature based on the variation of a chromatin feature is a productive approach to define signal-responsive genomic elements. Further, our study implicates global epigenetic modifications in rapid, signal-responsive transcriptional regulation.